A Bibliometric Review on Risk Management and Building Information Modeling for International Construction - Ganbat, T.; Chong, Heap Yih; Liao, P.; Wu, Y. (Hindawi Publishing Corporation, 2018)
International construction is complicated and involves high risks. However, with the development of technological innovation, Building Information Modeling (BIM) emerged and seems to be able to address certain risks. To understand BIM applications in risk management for international construction, a state-of-the-art review is required. Therefore, this paper aims to identify the research trends and opportunities for risk management in BIM-enabled international construction by reviewing 526 peer-reviewed journal articles for the years 2007-2017. Thus five steps of bibliometric analysis were conducted based on the proposed frameworks of BIM risk management in international construction (BIM-RM-INTL). The results show that the popularization of BIM not only attracts all stakeholders' interests but also brings some risks. For example, financial factors are hard to detect and control through BIM, information loss during transmission stands out, and BIM has no unified standards and regulations for international construction. The research has mapped existing research results and their relationships for future risk management in BIM-enabled international construction.